Manajemen Pembiayaan Pendidikan Dalam Membangun Kepercayaan Konsumen di Pondok Pesantren Darunnajah Jakarta - samiyono (Edukasiana: Journal of Islamic Education, 2024)
Abstract Darunnajah Islamic boarding school Jakarta, as one of the leading Islamic educational institutions in Indonesia, continues to strive to strengthen relationships of trust with consumers through effective education financing management. The background to this research includes the complexity of financial challenges faced by educational institutions in maintaining a balance between financial needs and consumer expectations for the quality of educational services. The research method used is a case study with a qualitative approach. Data was collected through in-depth interviews with managers and key stakeholders at the Darunnajah Islamic Boarding School, Jakarta, as well as analysis of documents related to education financing management. The research results show that the Darunnajah Jakarta Islamic Boarding School has succeeded in implementing a careful and adaptive education financing management strategy. These steps include diversification of funding sources, efficient financial management, and transparent policy implementation. In this way, this institution is able to strengthen consumer trust and maintain its reputation as a quality educational institution. Keywords: Education Financing, Consumer Confidence, and Financial Strategy.